1998
DOI: 10.1046/j.1365-277x.1998.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination of enteral feeding systems due to faulty handling procedures—a comparison of a new system with two established systems

Abstract: Background: The purpose of this study was to compare the risks of introducing microbial contamination when assembling and running two commonly used, ready‐to‐hang, enteral feeding systems (Nutrison glass bottles and Steriflo) with a newly introduced system (Nutrison pack). Methods: The nutrient container tops of all systems were deliberately touched during assembly by a researcher wearing gloves contaminated with Klebsiella aerogenes. After touching, half the containers were immediately connected to givi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The overall low growth seen in this study was much less than we premised given the increased manipulation of the EFS. This study design emulated a previous report by Beattie and Anderton 5 in 1998 where enteral feeding systems using both RTH and decanted formula were infused into a beaker with the tip of the EFS suspended above the fluid level to assess the impact of handling on bacterial growth. Investigators deliberately contaminated the hands of those who set up the initial EFS to determine the impact of bacterial contamination over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall low growth seen in this study was much less than we premised given the increased manipulation of the EFS. This study design emulated a previous report by Beattie and Anderton 5 in 1998 where enteral feeding systems using both RTH and decanted formula were infused into a beaker with the tip of the EFS suspended above the fluid level to assess the impact of handling on bacterial growth. Investigators deliberately contaminated the hands of those who set up the initial EFS to determine the impact of bacterial contamination over time.…”
Section: Discussionmentioning
confidence: 99%
“…Overall contamination rates of enteral formulas or the EFS are reported to be between 19% and 59% 3 , 4 , 5 8 . Sources of contamination have been identified to originate from any point in preparation to administration of formula.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Inadequate knowledge about enteral feeding (EF) among healthcare workers (HCWs) may lead to bacterial contamination of EF systems as a result of incorrect handling procedures. 9 Studies have shown that the major source of transmission of pathogens between patients is from contaminated hands of HCWs to clean environmental or skin sites, 10e13 and that areas such as flow regulators are contaminated by HCWs' hands. 8 Other sources of enteral feed contamination include inadequately cleaned equipment and poor kitchen/nursing home environment.…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out by Schreiner et al (1979) on decanting feeds for neonates and one carried out by Patchell et al (1994) on feeds intended for infants receiving enteral nutrition in hospital or at home have also demonstrated bacteria gaining entry to systems via this route. Assembly and manipulation of feeding systems have also been shown as procedures which can introduce bacteria into the systems (Schroeder et al 1983, Crocher et al 1986, Anderton and Aidoo 1988, Beattie and Anderton 1998, 1999 However, in a follow-up to their earlier study, Patchell et al (1998) demonstrated that staff education and modification of the enteral feeding protocol reduced both the levels and incidence of bacterial contamination. Also, studies by Anderton (1998, 1999) highlighted the important role played by system design in reducing the number of bacteria introduced into feeds during the assembly of systems and the delivery of the feed.…”
Section: Introductionmentioning
confidence: 99%